The Female Character Struggle to Obtain Equality in Beauty and the Beast - Muafiah, Rahmawati; Suryani, Suci (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2024)
In the patriarchy system, women have restriction in delivering thoughts and action, accessing education, and obtaining rights. However, they struggle hard to attain equality in those aspects in their life. Hence, the study aims to find out the restriction experienced by women character named Belle and how she fight against the restriction to obtain her freedom and independence as women. While the original